The Importance of Individual Education Plan (IEP) in Communicative Development of Children With Speech Delay: A Systematic Literature Review - Yuniari, Ni Made; Made Hery Santosa (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Lack of time with parents and lack of awareness of a child’s potential can cause speech delays. This research aims to analyze the role of Individual Education Plans (IEPs) on the communicative development of deaf children. This type of research is qualitative research. This study included a systematic literature review that included 14 studies on IEPs and speech delays. Collecting relevant data using systematic observation techniques. Systematic observation techniques were used to collect relevant data from several articles. The data analysis technique uses qualitative descriptive analysis. These findings underscore the need for IEPs to address the special needs of children with speech delays, the importance of individualized methods, the availability of appropriate resources and supports, and the participation of parents and other stakeholders in the IEP process. This study emphasizes the need to develop and implement high-quality IEPs, provide resources and assistance, and involve parents and stakeholders in help childrenhelpingh speech delays successfully. This study also briefly highlights the limitations and recommendations of the research evaluated, highlighting the need for collaborative and strengths-based IEPs, early intervention, family participation, and good communication with stakeholders. It can be concluded by emphasizing the importance of different interpretations, further research, and a holistic approach to inclusive education and the development of children’s speech abilities.